(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
AI can improve society if used wisely. Furthermore, there is a genuine possibility thatcommercial and governmental use will have a negative influence on human rights, as is the case with mostdeveloping technologies. The objective of this study focuses on how gaps challenges in AI will beaddressed, as well as how these issues may affect fundamental human rights concepts. These problemsinclude algorithmic openness, cyber security flaws, unfairness, bias, perception, lack of contestability,problems with legal personhood, problems with intellectual property, negative effects on workers,problems with privacy data protection, liability for harm, lack of accountability. In order to betterunderstand key areas of concern direct risk impact mitigation measures to safeguard human wellbeing,the analysis will use the concept of vulnerability.